Correlating the morphological changes to electrochemical performance during carbon corrosion in polymer electrolyte fuel cells. Issue 23 (30th May 2022) - Saha, Prantik; Khedekar, Kaustubh; Wang, Hanson; Atanassov, Plamen; Cheng, Lei; Stewart, Sarah; Johnston, Christina; Zenyuk, Iryna V.
Abstract : Carbon corrosion in catalyst layer of PEFCs showed two phases: in first 500 AST cycles carbon corroded rapidly and catalyst layer thickness was lost, after that corrosion slowed down but a pore structure collapsed, increasing O2 transport resistance. Abstract : A mechanistic understanding of carbon corrosion in polymer electrolyte fuel cells (PEFCs) is required to design durable catalyst layers. Uncontrolled startup and shutdown of PEFCs cause electrochemical oxidation of carbon, which leads to several degradation phenomena, such as loss in electrochemical surface area (ECSA), pore structure collapse or increase in mass transport resistance. In this study, the chronology of morphological changes in the cathode catalyst layer due to carbon corrosion was identified and correlated with electrochemical performance degradation. PEFCs were subjected to the Department of Energy carbon corrosion accelerated stress test (AST) protocol. The study revealed two phases: in the initial phase (∼500 AST cycles), amorphous carbon in contact with Pt nanoparticles oxidized fast. Rapid carbon loss and catalyst layer thinning occurred, but pore structure did not change significantly. Pt nanoparticles detached from the support and ECSA decreased drastically. In the second phase (∼1500 AST cycles), carbon corrosion slowed down, but severe pore structure collapse was observed. Porosity and pore connectivity within the cathode catalyst layer decreased considerably. Electrochemical diagnostics corroborated this finding by showing significantly higher O2 mass transport resistance. Lastly, no significant change was observed in the concentration of oxides on the carbon surface after AST. But overall water management in the cathode catalyst layer deteriorated as the pore structure collapsed. This study provides an in-depth understanding of morphological changes during PEFC carbon corrosion AST protocol and motivates novel material design strategies to enable durable PEFCs.